MENYIBAK TABIR POLITIK OTENTIKARENDTlAN: SEBUAH PEMBACAAN DARI PERSPEKTIF ETIKA POLITIK - Pius Pandor (Arete, 2013)
In philosophical discussions, politics is one of the most interesting, deep but also slippery topics. It is interesting because it aims to make life in society more humane, deep because it involves a variety of interests, and slippery because it is a discussion between citizens on various issues in a public space. This interesting, deep and slippery discourse is analysed by Hannah Arendt by clearly distinguishing between what is political and what is apolitical. In what is political, there are freedom and plurality. This becomes evident in the arena called "public space". On the other hand, what is apolitical can be defined as forcing the citizens into uniformity. According the Arendt, authentic politics has to be vivified by freedom, supported by plurality among human beings and strengthened by interlocution [communication] among citizens in public space.